History and general description of New France (1866) (14782238225) - Charlevoix | Pierre... (Wikimedia Commons, 1866)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie